-4.3-.1x=-6.1

Simple and best practice solution for -4.3-.1x=-6.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4.3-.1x=-6.1 equation:


Simplifying
-4.3 + -0.1x = -6.1

Solving
-4.3 + -0.1x = -6.1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4.3' to each side of the equation.
-4.3 + 4.3 + -0.1x = -6.1 + 4.3

Combine like terms: -4.3 + 4.3 = 0.0
0.0 + -0.1x = -6.1 + 4.3
-0.1x = -6.1 + 4.3

Combine like terms: -6.1 + 4.3 = -1.8
-0.1x = -1.8

Divide each side by '-0.1'.
x = 18

Simplifying
x = 18

See similar equations:

| (5a-1)(6a-3)= | | -15+5x=11+3x | | 0=2x+10 | | -5+5x=11+3x | | 0=x+5 | | 0=x-1 | | -2+3x=14+5x | | 8-1=63 | | 0.12(6)+0.02x=0.04(12+x) | | -9v+9=10(8v-8) | | 0.12y+0.09(y+4000)=1410 | | -2(x+16)+3(2x-5)=3(x-4)+10 | | 5x+26=2x+98 | | 2(4x-1)+3(3-2x)=0 | | 7+n=2n | | 4x+17=8x+10 | | 3a-9=7+3a-a | | 6x-3(x+9)=5x-17 | | (3x^2)+18x-16=2-7x | | 3(x-11)=14*34(16+x)-78 | | -6(3m-10)=6-9m | | 30y^2-25y+5=0 | | y^2-121=0 | | y+5=10 | | -[8z-(15z+8)]=8+(6z+2) | | -17p-5(2-5p)=4(p-4)-38 | | X^2+25x+600=0 | | -24=v+2 | | x^2+4x+2=y | | x-14=22 | | 2.7-2y=3 | | -19=14+x |

Equations solver categories